The phytochemistry and biological activities of Athrixia Phylicoides - Padayachee, Kumeshnie (My University, 2011)
Herbal medicines are an important part of the African culture and tradition and about 80% of Africa’s population relies on traditional remedies for their primary health care needs (WHO, 2008). Athrixia phylicoides is widely used as a traditional remedy, but despite its substantial use, literature on its chemical composition and biological activities is limited. In this study, the chemical composition of the essential oil was determined using gas chromatography combined with mass spectroscopy (GC/MS) and analysis resulted in the identification of 182 compounds. The major compounds identified in selected samples were α-pinene, β-pinene, caryophyllene oxide, β-caryophyllene, myrcene and spathulenol. Based on the traditional uses of A. phylicoides, various in vitro biological activities were investigated. The extensive use of A. phylicoides for the treatment of boils, sores, bad acne, infected wounds and cuts, prompted the antimicrobial (bacterial and fungal) study using the minimum inhibitory concentration (MIC) assay. The methanol extract and essential oil were more selective for the Grampositive bacteria than the Gram-negative bacteria. The extract exhibited stronger activity against all micro-organisms tested compared to the essential oil, with the highest activity against S. aureus, B. cereus and B. subtilis (MIC = 1 mg/ml). The bioactive compound, (4-hydroxyphenyl) propyl coumaroate was isolated from the extract and proved to be most active against S. aureus (MIC = 19.5 μg/ml). Using the DPPH• assay, a comparative antioxidant study was performed. The anti-oxidant activity of the aqueous extract of A. phylicoides (IC50 = 14.01 ± 2.68 μg/ml) was greater than rooibos and Ceylon (black) tea (IC50 > 25.00 μg/ml); comparable to green rooibos and honeybush tea (IC50 = 18.01 ± 4.06 μg/ml; 18.02 ± 4.27 μg/ml, respectively), but less active than green tea (IC50 = 9.64 ± 0.96 μg/ml). The antimalarial activity was determined using the [3H] hypoxanthine incorporation method. The essential oil exhibited greater antimalarial activity against the chloroquine-resistant Plasmodium falciparum (FCR-3) strain (IC50 = 1.006 ± 0.06 μg/ml) than the methanol extract. The 5-lipoxygenase assay was used to assess the anti-inflammatory activity of the methanol extract and essential oil. Only the essential oil displayed anti-inflammatory activity (IC50 = 25.68 μg/ml). Low safety indices were reported for both the methanol extract (SI = 2.28) and essential oil (SI = 1.77). The in vitro biological activities may validate the use of A. phylicoides in traditional medicine.
Keywords: herbal teas; antimicrobial activities; antioxidant activities; Athrixia phylicoides; Zulu tea; Bushman's tea; Bush tea